Understanding Sexual Minority Male Students’ Meaning-Making About Their Multiple Identities: An Exploratory Comparative Study - Tillapaugh, Daniel (Canadian Journal of Higher Education, 2016)
This exploratory comparative study examines the meaning-making experiences of six sexual minority males attending college or university in Canada or the United States. All of the participants identified as sexual minority males who were cisgender, out to family and/or friends, and between 20 and 24 years of age. In particular, the participants spoke about the intersections between their race, gender, and sexual orientation as salient aspects of their multiple identities. Using a blend of qualitative methods, including case study, phenomenology, and grounded theory, I identified four themes that emerged from the data: (1) engagement in a social justice curriculum; (2) involvement in LGBT student organizations or resource centres; (3) experiences of discrimination and dissonance; and (4) engagement in reflective dialogue. I discuss the implications of these themes for professional practice and future research.